PERWUJUDAN KASIH SAYANG KELUARGA DAN KERABAT MELALUI PERTUNJUKAN TOR-TOR - Novita, Elmi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
Affection is a very important relationship in social life. Affection is manifested in various ways, one of which is performing art. This study explains the manifestation of affection between family and relatives in Mandailing culture. The research method is carried out through observation of tor-tor performances, which are performances that combine dance, music, and literature that become Mandailing culture. The results showed that affection in Mandailing culture is an important part of the kinship values of dalihan na tolu. Affection called holong is a noble value that governs relationships in kinship groups dalihan na tolu. Holong became one of the identities attached to the Mandailing community. In line with Islamic values and Mandailing cultural norms, compassion is felt with the heart and is not expressed openly either through touch or eye contact between families during tor-tor performances. The affection of family and relatives in dancing arises in response to togetherness in dancing and song verses that tell the life experiences of family and relatives.Keywords: Affection, kinship, identity, performing arts. AbstrakKasih sayang adalah hubungan yang sangat penting dalam kehidupan sosial. Kasih sayang diwujudkan dalam berbagai cara, salah satunya seni pertunjukan. Penelitian ini menjelaskan perwujudan kasih sayang antara keluarga dan kerabat di kebudayaan Mandailing. Metode penelitian dilakukan melalui pengamatan terhadap pertunjukan tor-tor, yaitu pertunjukan yang menggabungkan tari, musik dan sastra yang menjadi kebudayaan Mandailing. Hasil penelitian menunjukkan kasih sayang di kebudayaan Mandailing merupakan bagian penting dari nilai-nilai kekerabatan dalihan na tolu. Kasih sayang yang disebut dengan holong merupakan nilai luhur yang mengatur hubungan dalam kelompok kekerabatan dalihan na tolu. Holong menjadi salah satu identitas yang melekat dengan masyarakat Mandailing. Sejalan dengan nilai-nilai Islam dan norma budaya Mandailing kasih sayang dirasakan dengan hati dan tidak diungkapkan secara terbuka baik melalui sentuhan ataupun kontak mata diantara keluarga selama pertunjukan tor-tor. Kasih sayang keluarga dan kerabat dalam menari timbul sebagai tanggapan terhadap kebersamaan dalam menari dan syair lagu yang menceritakan pengalaman hidup keluarga dan kerabat.Kata Kunci: Kasih sayang, kekerabatan, identitas, seni pertunjukan Author:Elmi Novita : Institut Seni Budaya Indonesia Aceh ReferencesAdiriani, and Nova Fitriani. 2023. œMotif Dan Makna Motif Tenun Ulos Batak Angkola Di Kabupaten Tapanuli Selatan. Gorga: Jurnal Seni Rupa 12(2):302“9. doi: 10.24114/gr.v12i2.49593.Alamo, Enrico, Meria Eliza, and Giat Syailillah. 2021. œMakna Dan Fungsi Kain Ulos Pada Pusat Latihan Opera Batak Pematang Siantar (PLOt) Di Pematang Siantar Provinsi Sumatera Utara. Gorga: Jurnal Seni Rupa 10(1):94“106. doi: 10.24114/gr.v10i1.24824.Blacking, John. 1982. œMovement and Meaning: Dance in Social Anthropological Perspective. Dance Research: The Journal of the Society for Dance Research 1 (1):88“99.Budrianto, Wilma Sriwulan, and Marta Rosa. 2018. œApropriasi Gitar Dalam Kesenian Rejung Pada Masyarakat Suku Bashemah Kabupaten Kaur Provinsi BEngkulu. Gorga: Jurnal Seni Rupa 7(2):94“100. doi: 10.24114/gr.v7i2.10915.Buelow, George J. 1973. œMusic, Rhetoric, and the Concept of the Affections: A Selective Bibliography. Notes 30(2):250“59. doi: 10.2307/895972.Burleson, Mary H., Nicole A. Roberts, David W. Coon, and JosÃ© A. Soto. 2019. œPerceived Cultural Acceptability and Comfort with Affectionate Touch: Differences between Mexican Americans and European Americans. Journal of Social and Personal Relationships 36(3):1000“1022. doi: 10.1177/0265407517750005.Dissanayake, Ellen. 1992. Homo Aestheticus¯: Where Art Comes From and Why. Seatle: University of Washington Press.Dyck, Edith Van, Birgitta Burger, and Constantina Orlandatou. 2017. œThe Communication of Emotions in Dance. Pp. 122“30 in The Routledge Companion to Embodied Music Interaction, edited by M. Lesaffre, P.-J. Maes, and M. Leman. New York and London: Routledge, Taylor & Francis Group.Floyd, Kory. 2006. Communicating Affection: Interpersonal Behavior and Social Context. Cambridge: Cambridge University Press.Gabrielsson, Alf. 2016. œThe Relationship between Musical Structure and Perceived Expression. Pp. 215“32 in The Oxford Handook of Music Psychology, edited by S. Hallam, I. Cross, and M. Thaut. New York, USA: Oxford University Press.Hall, Stuart. 1997. Representation: Cultural Representation and Signifying Practices. London: Sage Publications.Haosheng, YE, SU Jiajia, and SU Dequan. 2021. œThe Meaning of the Body: Enactive Approach to Emotion. Acta Psychologica Sinica 53(12):1393“1404. doi: https://doi.org/10.3724/SP.J.1041.2021.01393.Kottak, Conrad Phillip. 2005. Mirror for Humanity: A Concise Introduction to Cultural Anthropology. Fifth Edition. New York: McGraw-Hill Higher Education.Lang, Paul Henry. 1967. œThe Enlightenment and Music. Eighteenth-Century Studies 1(1):93“108. doi: 10.2307/3031668.Miles, Mattew. B., and Michael A. Huberman. 1994. Qualitative Data Analysis: An Exspanded Sourcebook. 2nd ed. Beverly Hills, CA: Sage Publications.Nasution, Edi. 2007. Muzik Bujukan Mandailing. Penang, Malaysia: Areca Book.Novita, Elmi. 2024. œSeni Pertunjukan Tor-Tor Pembangun Identitas Komunitas Mandailing Di Kabupaten Rokan Hulu, Provinsi Riau. Disertasi, Institut Seni Indonesia Surakarta, Surakarta.Novita, Elmi, Santosa Soewarlan, and Nyoman Sukerna. 2022. œManortor as a Solidarity and Identity Building Media of Mandailing Ethnic Group in Rokan Hulu, Riau Province. Harmonia: Journal of Arts Research and Education 22(2):355“67. doi: http://dx.doi.org/10.15294/harmonia.v22i2.36753.Peick, Melissa. 2005. œDance as Communication: Messages Sent and Received through Dance. Journal of Undergraduate Research VIII 1“9.Rahmadani, Suci, and Erlinda. 2019. œMakna Simbolik Tor-Tor Toping Huda Dalam Upacara Adat Sayumatua Pada Masyarakat Simalungun Sumatera Utara. Gorga: Jurnal Seni Rupa 08(01):61“67. doi: 10.24114/gr.v8i1.12786.Zardi, Andrea, and Rosalba Morese. 2021. œDancing in Your Head: An Interdisciplinary Review. Frontiers in Psychology 12:1“14. doi: https://doi.org/10.3389/fpsyg.2021.649121.